Distinct effects of Disabled‐2 on transferrin uptake in different cell types and culture conditions. (6th June 2014) - Chu, Hui‐Chun; Tseng, Wei‐Lien; Lee, Hsing‐Ying; Cheng, Ju‐Chien; Chang, Shy‐Shin; Yung, Benjamin Yat‐Ming; Tseng, Ching‐Ping
Abstract Iron uptake by the transferrin (Tf)‐transferrin receptor (TfR) complex is critical for erythroid differentiation. The mechanisms of TfR trafficking have been examined, but the adaptor proteins involved in this process are not fully elucidated. We have investigated the role of the adaptor protein, Disabled‐2 (Dab2), in erythroid differentiation and Tf uptake in the cells of hematopoietic lineage. Dab2 was upregulated in a time‐dependent manner during erythroid differentiation of mouse embryonic stem cells and human K562 erythroleukemic cells. Attenuating Dab2 expression in K562 cells diminished TfR internalization and increased surface levels of TfR concomitantly with a decrease in Tf uptake and erythroid differentiation. Dab2 regulated Tf uptake of the suspended, but not adherent, cultures of K562 cells. In contrast, Dab2 is not involved in TfR trafficking in the HeLa cells with epithelial origin. These differential effects are Dab2‐specific because attenuating the expression of adaptor protein 2 μ subunit inhibited the uptake of Tf regardless of culture condition. We offer novel insight of Dab2 function in iron uptake and TfR internalization for the suspended culture of hematopoietic lineage cells.